Reliability analysis of power system with high penetration of renewables and energy storages - Guo, Hui (Nanyang Technological University, 2023)
Conventional power system analysis is based on fossil energy sources and conventional loads, often excluding the integration of renewables and energy storage systems. The paper begins with analyzing the current global status of renewable energy development, emphasizing the necessity of promoting renewable energy and further highlighting its significance in conjunction with the characteristics of nuclear energy. The second section initially introduces the reliability model of conventional power generators, followed by a focused analysis of the output characteristics of wind and solar photovoltaic power generation. For wind power, the impacts of wind speed and equipment faults on its reliability are considered; for solar PV power, the fluctuations in solar resources and system structural features are taken into account, leading to the establishment of corresponding reliability models. In the third section, traditional load models including time-varying, average, and load duration models are introduced. Subsequently, various types of energy storage systems are presented, along with an analysis of their pros and cons. Then energy storages are integrated into the load model, particularly within the Load Duration Model. The paper then outlines power system reliability evaluation methods, with a specific focus on explaining the significance and calculation methods of Loss of Load Expectation (LOLE) and Expected Energy Not Supplied (EENS). In the final section, the study incorporates specific parameters based on the preceding content. Four scenarios are postulated based on the presence of renewable energy and energy storage devices, and their reliability parameters are computed and compared. The conclusion is drawn that integrating renewables and energy storage has significant implications for power system reliability. Proper management of these technologies can enhance resilience and stability, but challenges should be addressed for consistent power supply while meeting user needs.